Students’ communication skills and creativity in learning biotechnology with discovery learning combined with role-playing on - Ningrum, Fahdilah Cahya; Rinanto, Yudi; Santosa, Slamet (Biosfer: Jurnal Pendidikan Biologi, 2025)
Biotechnology is often seen as a difficult topic to be understood by students due to the prevalence of foreign terms and complex concepts. Therefore, a suitable, effective, and engaging learning method is essential. This research aims to determine an engaging learning method, namely role-playing, to enhance students’ communication skills and creativity. This role-playing learning method is integrated with the discovery learning model. This research is quantitative research with a quasi-experimental model. This study used instruments in the form two types of post test questions, namely questions to determine communication skills and questions to determine student creativity after the experiment was conducted. Distributed in two classes used after two learning meetings in class. These results indicate the differences in communication skills and student creativity before and after the application of the role-playing learning method. The results indicate that the application of role-playing learning can facilitate the development of students’ communication skills and creativity.